COVID-19, PANDEMI BAYANGAN, DAN AKSES TERHADAP KEADILAN BAGI KAUM MUDA KORBAN KEKERASAN DALAM RUMAH TANGGA - Saputra, Eno; Anggara, Ari; Husaini, Husaini; Salasa, Ricco; Haryadi, Donni; Rafik, M.; Fikri, KMS Novyar Satriawan (Bhinneka Multidisiplin Journal, 2025)
The COVID-19 pandemic has co-existed alongside a far less visible “shadow pandemic” of violence against women, with COVID-19 impacting the number and complexity of domestic violence cases and enabling new tactics for coercive control. This article provides a preliminary assessment of the extent to which Canada’s responses to the COVID-19 pandemic have prioritized the safety of women and children, with a focus on the courts and women’s access to justice. We examine court directives and judicial decisions triaging which cases would be heard as “urgent,” as well as courts’ decisions on the merits in cases involving domestic violence and COVID-19, spanning the areas of family, child welfare, criminal law, and civil protection orders. In the sixty-seven reported decisions in our sample, we find very little awareness overall of the heightened risks for survivors during COVID-19, in keeping with the prepandemic tendency of decision makers to focus on incident-based physical violence instead of patterns of coercive control. Our analysis also suggests that survivors’ability to  prove domestic violence and secure court orders that would help to ensure their safety was hampered not only by procedural complexity but also by the reduced availability of a range of services—health, counselling, housing, and supervised access centres, for example as a result of COVID-19